Proceedings of the 13th International Conference on Web Search and Data Mining 2020
DOI: 10.1145/3336191.3371844
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Treatment of Learning to Rank Scoring Functions

Abstract: Learning to Rank, a central problem in information retrieval, is a class of machine learning algorithms that formulate ranking as an optimization task. The objective is to learn a function that produces an ordering of a set of documents in such a way that the utility of the entire ordered list is maximized. Learning-to-rank methods do so by learning a function that computes a score for each document in the set. A ranked list is then compiled by sorting documents according to their scores. While such a determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…Recently, Bruch et al [4] demonstrate that learning to rank models can be optimized towards expected values of relevance metrics computed over multiple rankings sampled based on estimated relevance. While not developed in the context of deploying a stochastic ranker, we adopt some of the methodologies therein in our experiments.…”
Section: Stochastic Rankingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bruch et al [4] demonstrate that learning to rank models can be optimized towards expected values of relevance metrics computed over multiple rankings sampled based on estimated relevance. While not developed in the context of deploying a stochastic ranker, we adopt some of the methodologies therein in our experiments.…”
Section: Stochastic Rankingmentioning
confidence: 99%
“…Unfortunately, this sampling process is non-differentiable and, therefore, prohibitive to a large class of models, including those that learn by gradient descent. We address this by adopting the method proposed by Bruch et al [4]. To construct a sampled ranking , we reparameterize the probability distribution by adding independently drawn noise samples from the Gumbel distribution [23] to y and sorting items by the "noisy" probability distributioñ ,˜(…”
Section: Algorithmmentioning
confidence: 99%
“…It is noteworthy, that enumerating all distinct document permutations can be computationally challenging even for a moderately sized set of candidates. More recently, Bruch et al [418] demonstrated a mechanism for sampling rankings from the Plackett-Luce distribution using the reparameterization trick [395] that is amenable to gradient-based optimization. Their approach involves adding independently drawn noise samples from the Gumbel distribution [419] and then deriving the approximate rank of the document following the method proposed by Qin et al [420] and Wu et al [421].…”
Section: Related Workmentioning
confidence: 99%
“…For our experiments, we use two public learning-to-rank datasets with numerical features, and two large-scale proprietary datasets. 3 We discard queries with no relevant documents, similar to evaluation in [4]. ick Access.…”
Section: Experiments 51 Datasetsmentioning
confidence: 99%
“…On the public datasets, we compare attn-DIN with the RankLib 4 and LightGBM [10] implementations of LambdaMART, and state-of-theart neural ranking algorithms: SetRank [14], Deep Listwise Context Model (DLCM) [1], Groupwise Scoring Functions (GSF) [2], and Feed-Forward Neural Network (with ReLU activations) with Gumbel Approximate NDCG loss [3]. We tune the hyperparameters of LightGBM and set both the number of iteration and the number of leaves to be 2,000 for WEB30K and 500 for Istella.…”
Section: Baselinesmentioning
confidence: 99%